Pengaruh Ekstrak Seledri (Apium graveolens L.) Terhadap Kelarutan Kalsium Dalam Batu Ginjal - Dewi, Evie Kurnia Maya; Walanda, Daud K.; Sabang, Sri Mulyani (Universitas Tadulako, 2016)
Celery (apium graveolens L.) contains chemicals that can be used as traditional medicine for various treatments. The research objective is to determine the effect of celery (apium graveolens L.) extractsin dissolving calcium kidney stones and calcium to determine the relationship between the concentration of extract of celery (apium graveolens L.) with the solubility of calcium in the kidney stones. Determination of the solubility of calcium in an extract of celery is by flame fotometer. The concentration of the extract was varried into 1, 5, 10, 15 and 20%. It showed that a concentration of 1% can dissolve the calcium as much as 15.104%; concentration of 5% can dissolve the calcium as much as 18.708%; concentration of 10% can dissolve the calcium as much as 23.683%; concentration of 15% can dissolve the calcium as much as 28.869%; and to a concentration of 20% can dissolve the calcium as much as 35.048%. It can be concluded that celeries extract can dissolve calcium of kidney stones.